Water, sky and cultural territories as expanded heritage. New spatialities to rethink the Venice charter-contributions from south America - Sudar Klappenbach, Luciana (2024)
Fil: Sudar Klappenbach, Luciana. Universidad Nacional del Nordeste. Facultad de Artes, Diseño y Ciencias de la Cultura; Argentina.